(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
From last years, fractals and the study of their dynamics is one of the emerging and attractive areas for mathematicians. A Fractal is a geometric shape each part of which has the same characteristics as the original one. By zooming a fractal, one can find that the patterns and shapes will continue repeating, forever. In this paper, I present a brief survey on fractals.